Pollen morphology of Napeantheae Wiehler (Gesneriaceae) from Brazil - Bellonzi, Talita Kely; Gasparino, Eduardo Custódio [UNESP] (Taylor & Francis, 2022)
Napeantheae is a monogeneric tribe of Gesneriaceae (with Napeanthus Gardner), that presents species with different morphology from other Gesnerioideae, being herbs with rosulate leaves that grow in pits, banks or at the base of rocks in humid forests. The tribe's palynology is poorly known. Thus, the aim of this study was to investigate the pollen morphology of the Brazilian native species of Napeanthus (Napeantheae) in order to expand the morphological knowledge of the tribe and compare it with existing studies on Gesneriaceae. For the analysis, the pollen grains were removed from flower buds of exsiccatae deposited in herbaria; they were acetolyzed, measured, photographed using light microscopy (LM) and scanning electron microscopy (SEM), and described qualitatively. The analyzed species present differences in amb, polar area, shape, size of ectoapertures, type of endoapertures and exine thickness. The pollen grains are monads, isopolar, small, tricolporate, circulaperturate, ectoaperture rounded at the polar ends and without margo; the exine is semitectate, microreticulate-fossulate, sexine is thicker than nexine. An artificial pollen key is presented to help distinguish species. Quantitative pollen grain data confirm the qualitative differences observed, especially in relation to the type of endoaperture. The microreticulate-fossulate exine ornamentation observed in Napeanthus has not previously been recorded for Gesneriaceae, especially in Gesnerioideae.
Keywords: Brazilian species; Gesnerioideae; palynology; palynotaxonomy; pollen grains